Carbon-doped molybdenum nitride nanobelt electrocatalyst and preparation method thereof
Patent Information
- Application Number
- CN202110773250.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-08
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2041-07-08
AI Technical Summary
现有氮化钼纳米材料在碱性HER过程中催化活性无法与贵金属基催化剂相媲美,主要由于氮元素对过渡金属单一的调节作用无法实现HER氢物种的选择性吸/脱附。
Mo-PTI was synthesized by ion exchange and carbon-doped molybdenum nitride nanoribbons (C-Mo2N/NC) were prepared by high-temperature annealing. The amino groups of the triazine ring derivatives were used to form multi-terminal coordination supports to avoid aggregation. The nanoribbon morphology exposed active sites, and the electronic structure was adjusted by carbon doping.
It improves the HER efficiency and stability of the catalyst, exhibits excellent electrocatalytic activity, has significant cost advantages, and good kinetic performance.
Smart Images

Figure CN115595615B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrocatalytic water-to-hydrogen technology, specifically relating to a method for preparing a carbon-doped molybdenum nitride nano-electrolyte catalyst. Background Technology
[0002] Platinum-based materials are the most effective electrocatalysts for electrocatalysts for water splitting; however, the scarcity and high cost of these noble metal-based catalysts severely hinder their large-scale application in water electrocatalysis. Among the many catalytic materials that can replace noble metals, molybdenum nitride (Mo) is a promising candidate. x Molybdenum (Mo, x = 0.5, 1, 2, etc.) has attracted widespread attention due to its unique transition metal d-band electronic structure, good electronic conductivity, and excellent stability. Because nitrogen is highly electronegative, the shared electron pair between Molybdenum and nitrogen atoms shifts significantly towards the nitrogen atom, creating partial vacancies in the d orbitals of Molybdenum. This results in a positively charged surface and a prominent adsorption effect on various oxygen species in aqueous solutions. This property not only endows Molybdenum with… x Nitrogen (N) holds great promise for applications in OER (Organic Emission Reduction) and is expected to significantly accelerate the reaction kinetics of basic HER (Hydrogen-Electrochemical Reaction). Therefore, molybdenum nitride (MoN) has become a highly promising HER material. Among the widely reported molybdenum nitride modification strategies, atomic-level size control, doping with non-metallic heteroatoms such as phosphorus and carbon, alloying with transition metal atoms such as cobalt and nickel, and the construction of heterojunctions are common. The aim is to achieve the desired MoN modification through electronic structure adjustment. x Nitrogen-based nanomaterials selectively adsorb / desorb oxygen or hydrogen species, ultimately achieving highly efficient HER catalytic activity.
[0003] Although Mo x Nitrogen nanomaterials exhibit good stability in alkaline HER processes, but their catalytic activity still cannot compare with that of noble metal-based catalysts such as platinum, ruthenium, and iridium. This is mainly due to the limitation of nitrogen's single regulatory effect on transition metals, which prevents it from achieving selective adsorption / desorption of hydrogen species in HER. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing carbon-doped molybdenum nitride nanoribbon electrocatalysts. First, a triazine ring derivative is thermally polymerized to obtain a water-soluble polytriazine-based material; then, a uniformly grown carbon-doped molybdenum nitride nanoribbon material is obtained through ion exchange and high-temperature annealing, which exhibits excellent HER activity.
[0005] The technical solution for realizing the present invention is:
[0006] A carbon-doped molybdenum nitride nano-electrolyte catalyst and its preparation method include the following steps:
[0007] Step 1: Synthesis of Mo-PTI via ion exchange method
[0008] 2,5,8-triaminosodium-melamine derivative (Na-PTI) was prepared into an aqueous solution and thoroughly mixed with a DMF solution of molybdenum acetylacetonate. After stirring and refluxing, the mixture was cooled to a certain temperature and stirred for a period of time to carry out ion exchange. After freeze-drying, Mo-PTI nanoribbons were obtained.
[0009] Step 2: Annealing treatment to prepare carbon-doped molybdenum nitride nanoribbons (C-Mo2N / NC)
[0010] The Mo-PTI obtained in step one is placed in a vacuum-sealed tube and annealed to obtain carbon-doped molybdenum nitride (C-Mo2N / NC) nanoribbons, which are high-efficiency electrocatalysts.
[0011] Preferably, in step 1, the concentration of the aqueous solution of sodium 2,5,8-triaminosodium-melamine derivative (Na-PTI) is 0.01M.
[0012] Preferably, in step 1, the mixture is first stirred and refluxed at 100-140°C for 2 hours, and then cooled to 0-20°C and stirred for another 0.5-1 hours.
[0013] Preferably, in step 2, the annealing treatment is carried out at 500-800℃ for 4 hours, and the more preferred annealing temperature is 700℃.
[0014] Compared with the prior art, the present invention has the following advantages:
[0015] (1) In the preparation of the precursor, the present invention introduces a 2,5,8-triaminosodium-melamine derivative and utilizes the characteristic that the abundant amino groups at the edge of the triazine small molecule can easily form hydrogen bonds to construct a multi-terminal coordinated support, while avoiding the aggregation of molybdenum nitride during heat treatment.
[0016] (2) The material prepared by this invention is in the form of nanoribbons. Its special morphology can expose more active sites during the catalytic process and improve HER efficiency.
[0017] (3) The final material of this invention is nano-sized carbon-doped molybdenum nitride. Heteroatom carbon doping can further regulate the electronic structure of molybdenum nitride and further improve its catalytic activity. Compared with traditional noble metal-based catalysts, it has a greater cost advantage. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the preparation process of a carbon-doped molybdenum nitride nano-electrolyte catalyst according to the present invention.
[0019] Figure 2 For Na-PTI in each embodiment 13 C10 NMR spectrum.
[0020] Figure 3This is a SEM image of Mo-PTI-T0 in Example 1.
[0021] Figure 4 The images shown are (a) SEM images and (b) XRD patterns of the C-Mo2N / NC-T0 sample in Example 1.
[0022] Figure 5 The images show the (a) LSV curve and (b) Tafel curve of the C-Mo2N / NC-T0 sample in Example 1.
[0023] Figure 6 The images shown are (a) SEM images and (b) XRD patterns of the Mo-PTI-T1 sample in Example 2.
[0024] Figure 7 The images shown are (a) SEM images and (b) XRD patterns of the Mo-PTI-T2 sample in Example 3.
[0025] Figure 8 (a) SEM image and (b) XRD image of the Mo-PTI-rate3 sample in Comparative Example 5.
[0026] Figure 9 (a) LSV curve and (b) Tafel curve of the C-Mo2N / NC-T1 sample in Comparative Example 9.
[0027] Figure 10 (a) LSV curve and (b) Tafel curve of the C-Mo2N / NC-T2 sample in Comparative Example 10.
[0028] Figure 11 (a) LSV curve and (b) Tafel curve of the C-Mo2N / NC-T3 sample in Comparative Example 11. Detailed Implementation
[0029] The present invention will be further described below with reference to specific embodiments and accompanying drawings.
[0030] This invention provides a molybdenum nitride catalyst with a well-defined micro / nano structure and controllable electronic structure, which is of great significance for achieving efficient water electrolysis to produce hydrogen. This invention synthesizes a novel carbon-doped molybdenum nitride nanoribbon, which achieves the goal of regulating the electronic structure of molybdenum nitride through carbon doping, ultimately exhibiting excellent HER activity as an electrocatalyst.
[0031] Combination Figure 1 The present invention discloses a method for synthesizing a carbon-doped molybdenum nitride nano-electrolyte, comprising the following steps:
[0032] Step one, the preparation of sodium 4,6-diamino-1,3,5-triazine-2-iminosodium salt (Na-Melamine) by the addition reaction of dicyandiamine and sodium cyanamide in the presence of potassium hydroxide catalyst, is as follows:
[0033]
[0034] Step two, under argon protection, involves the high-temperature polymerization of 4,6-diamino-1,3,5-triazine-2-iminosodium salt to prepare 2,5,8-triaminosodium-melamine derivative (Na-PTI). The process is as follows:
[0035]
[0036] Step 3: Dissolve the Na-PTI synthesized in Step 2 in water and dissolve molybdenum acetylacetonate in N,N-dimethylformamide (DMF). After thoroughly mixing the two, reflux and stir at a hot temperature. Continue stirring at a low temperature, centrifuge, wash, and freeze-dry to obtain a white molybdenum-containing precursor (Mo-PTI).
[0037] Step four: Place the Mo-PTI obtained in step three into a vacuum-sealed quartz tube, and anneal the tube in a muffle furnace to finally obtain carbon-doped molybdenum nitride nanoribbons (C-Mo2N / NC).
[0038] The Na-PTI used in the following examples was prepared through the following steps:
[0039] Step 1: Weigh 1.53 g (18 mmol) dicyandiamine, 0.95 g (15 mmol) sodium cyanamide, and 0.30 g (5 mmol) potassium hydroxide into a three-necked flask. Add 10 mL of DMSO solvent, and then heat and stir at 165 °C for 24 h using an oil bath. After the reaction is complete, pour the yellow transparent solution into 60 mL of ethanol and stir for 2 h. After filtration, a white product is obtained. The precipitate is then washed with DMF and ethanol and dried at 60 °C for 12 h. The dried product is named sodium 4,6-diamino-1,3,5-triazine-2-iminocyanide (Na-Melamine).
[0040] Step 2: Weigh 1.00 g of Na-Melamine obtained in Step 1 and place it in a porcelain boat. Heat the boat to 315 °C in a tube furnace at a rate of 5 °C / min under an argon flow rate of 80 mL / min, hold for 4 h, and allow to cool naturally. Wash the resulting yellow product with ethanol and DMF, respectively, and dry at 60 °C for 12 h to obtain the 2,5,8-triaminosodium-melamine derivative, named Na-PTI. Figure 2 For Na-PTI 13 C10 NMR spectrum.
[0041] Example 1
[0042] Step 1: Weigh 30.00 mg of Na-PTI and dissolve it in 10 mL of water to form a clear solution; weigh 74.80 mg of molybdenum acetylacetonate and dissolve it in 10 mL of DMF, then add it dropwise to the Na-PTI solution. The mixture is then refluxed and stirred at 120 °C for 2 h, followed by stirring at 0 °C for 0.5 h. After centrifugation, a white product is obtained. The product is washed with DMF and water and then freeze-dried for 12 h. The product is labeled Mo-PTI-T0. Figure 3 The SEM image of Mo-PTI-T0 shows that the synthesized material is a uniform nanoribbon material.
[0043] Step 2: Weigh 30.00 mg of Mo-PTI and place it in a specially made quartz tube. Vacuum seal the tube, then anneal it in a muffle furnace. The temperature is increased to 700℃ at a rate of 2℃ / min and held for 4 hours. After cooling to room temperature, a black powder sample is obtained. The product is labeled C-Mo2N / NC-T0, which is the high-efficiency HER catalyst. Figure 4 The images show (a) SEM and (b) XRD patterns of C-Mo2N / NC-T0. It can be seen that the annealed sample has small deformation and still has a nanoribbon structure, and it corresponds to the standard Mo2N card in the XRD.
[0044] Electrocatalytic hydrogen production (HER) activity test:
[0045] 2 mg of C-Mo2N / NC-T0 was weighed and dispersed in 400 μl of deionized water, 100 μl of isopropanol, and 20 μl of Nafion (5 wt%) dispersion. The mixture was sonicated for 40 min. 10 μl of the dispersion was pipetted onto a 5 mm diameter glassy carbon electrode and dried at room temperature to obtain a catalyst film (glassy carbon electrode loading was 0.02 mg / cm²). 2 Electrocatalytic testing was conducted using a three-electrode system. The working electrode was glassy carbon loaded with the sample, the carbon ribbon served as the counter electrode, and the mercury / mercury oxide electrode served as the reference electrode. The electrolyte was a 1M potassium hydroxide solution. Figure 5 Linear sweep voltammetry (LSV) of the HER for C-Mo2N / NC-T0 is shown in (a), and the Tafel curve is shown in (b). It can be seen that the current density reaches 10 mA / cm². -2 The overpotential was only 84 mV, indicating that C-Mo2N / NC has excellent electrocatalytic activity and a low Tafel value of 77.8 mV. -1 This demonstrates that the catalyst has good kinetic performance.
[0046] Example 2
[0047] The preparation of Mo-PTI nanoribbon materials was carried out using the same steps as in Example 1, except that the low-temperature method was changed. Specifically, the mixed solution was refluxed and stirred at 120°C for 2 hours, followed by stirring at 10°C for 0.5 hours. After centrifugation, a white product was obtained. The resulting precursor was named Mo-PTI-T1. Figure 6 Under these conditions, (a) SEM and (b) XRD of the precursor showed that there was no significant difference in morphology and structure between the precursor obtained in this example and that obtained in Example 1.
[0048] Example 3
[0049] The preparation of Mo-PTI nanoribbon materials was carried out using the same steps as in Example 1, except that the low temperature was changed. Specifically, the mixed solution was refluxed and stirred at 120°C for 2 hours, followed by stirring at 20°C for 0.5 hours. After centrifugation, a white product, Mo-PTI-T2, was obtained. Figure 7 (a) SEM and (b) XRD of the precursor under these conditions. From the comparison of SEM, it can be seen that the size of the Mo-PTI nanoribbons in this embodiment is slightly larger, and there is a tendency to transform into nanosheets; and the yield under the conditions of this embodiment is extremely low.
[0050] Example 4
[0051] The preparation of Mo-PTI nanoribbon materials was carried out using the same steps as in Example 1, except that the mass of molybdenum acetylacetonate was changed. Specifically, 30.00 mg of Na-PTI was weighed and dissolved in 10 mL of water to form a transparent solution; 37.40 mg of molybdenum acetylacetonate was weighed and dissolved in 10 mL of LDM, and then added dropwise to the Na-PTI solution. The final product contained very little insoluble matter.
[0052] Example 5
[0053] The preparation of Mo-PTI nanoribbon materials was performed using the same steps as in Example 1, except that the mass of molybdenum acetylacetonate was changed. 30.00 mg of Na-PTI was weighed and dissolved in 10 mL of water to form a transparent solution; 112.20 mg of molybdenum acetylacetonate was weighed and dissolved in 10 mL of LDM, and then added dropwise to the Na-PTI solution. The resulting precursor was named Mo-PTI-3rate. Figure 8 Under these conditions, (a) SEM and (b) XRD of the precursor showed that there was no significant difference in morphology and structure between the precursor obtained in this example and that obtained in Example 1.
[0054] Example 6
[0055] The preparation of Mo-PTI nanoribbon materials was carried out in the same manner as in Example 1, except that the low-temperature stirring treatment was not performed. Instead, the mixed solution was refluxed and stirred at 120°C for 2 hours, and no product was precipitated after cooling to room temperature.
[0056] Example 7
[0057] The preparation of Mo-PTI nanoribbon materials was carried out using the same steps as in Example 1, except that the reflux stirring temperature was changed. The mixed solution was refluxed and stirred at 100°C for 2 hours, followed by stirring at 0°C for 0.5 hours. After centrifugation, a white product was obtained. The experimental results of the final precursor were consistent with those of Example 1.
[0058] Example 8
[0059] The preparation of Mo-PTI nanoribbon materials was carried out using the same steps as in Example 1, except that the reflux stirring temperature was changed. The mixed solution was refluxed and stirred at 140°C for 2 hours, followed by stirring at 0°C for 0.5 hours. After centrifugation, a white product was obtained. The experimental results of the final precursor were consistent with those of Example 1.
[0060] Example 9
[0061] Carbon-doped molybdenum nitride nanoribbons were prepared using the same steps as in Example 1, except that the annealing temperature was changed. The temperature was increased to 500°C at a rate of 2°C / min and held for 4 hours. After cooling to room temperature, a black powder sample was obtained. The product was labeled C-Mo2N / NC-T1, which is the high-efficiency HER material. Figure 9 The experimental results show the HER activity under these conditions. (a) LSV indicates that 10 mA cm⁻¹ is reached. -2 (a) The overpotential at the given current density is 201 mV, and (b) the Tafel slope reaches 101.9 mV. -1 The poor catalytic performance is attributed to the low degree of carbonization caused by low-temperature annealing, resulting in a high resistance value during the catalytic activity experiment.
[0062] Example 10
[0063] Carbon-doped molybdenum nitride nanoribbons were prepared using the same steps as in Example 1, except that the annealing temperature was changed. The temperature was increased to 800°C at a rate of 2°C / min and held for 4 hours. After cooling to room temperature, a black powder sample was obtained. The product was labeled C-Mo2N / NC-T2, which is the high-efficiency HER material. Figure 10 (a) LSV indicates that it reaches 10 mA cm -2 (a) The overpotential at the given current density is 139 mV, and (b) the Tafel slope reaches 91.6 mV. -1 .
[0064] Example 11
[0065] Carbon-doped molybdenum nitride nanoribbons were prepared using the same steps as in Example 1, except that the annealing temperature was changed. The temperature was increased to 750°C at a rate of 2°C / min and held for 4 hours. After cooling to room temperature, a black powder sample was obtained. The product was labeled C-Mo2N / NC-T3, which is the high-efficiency HER material. Figure 11 (a) LSV indicates that it reaches 10 mA cm -2 (a) The overpotential at the given current density is 127 mV, and (b) the Tafel slope reaches 85.6 mV. -1 .
Claims
1. A method for preparing a carbon-doped molybdenum nitride nano-electrolyte catalyst, characterized in that, Includes the following steps: Step 1: Synthesis of Mo-PTI nanoribbons via ion exchange method An aqueous solution of sodium 2,5,8-triaminosodium-melamine derivative was thoroughly mixed with a DMF solution of molybdenum acetylacetonate. After stirring and refluxing, the mixture was cooled to a certain temperature and stirred for a period of time to carry out ion exchange. After freeze-drying, Mo-PTI nanoribbons were obtained. Step 2: Annealing treatment to prepare carbon-doped molybdenum nitride nanoribbons The Mo-PTI nanoribbons obtained in step one were placed in a vacuum-sealed tube and annealed to obtain a carbon-doped molybdenum nitride nanoribbon electrocatalyst. In step one, the mixture is stirred and refluxed at 100-140 °C for 2 h, and then stirred for another 0.5-1 h at 0-20 °C. Anneal at 500-800 °C for 4 hours.
2. The method as described in claim 1, characterized in that, In step one, the concentration of the aqueous solution of the 2,5,8-triaminosodium-melamine derivative is 0.01 M.
3. The method as described in claim 1, characterized in that, In step two, the sample is annealed at 700 °C for 4 hours.
4. The carbon-doped molybdenum nitride nano-charged catalyst prepared by the method according to any one of claims 1-3.
5. The use of the carbon-doped molybdenum nitride nanotube electrocatalyst prepared by any one of claims 1-3 in the electrocatalytic hydrogen evolution reaction.
Citation Information
Patent Citations
Ultrafine nitrogen-doped molybdenum carbide nanoparticle loaded on three-dimensional nitrogen-doped flower-shaped carbon spheres, as well as preparation method and application thereof
CN110787823A
Preparation method of two-dimensional coordination polymer electrocatalyst based on melem derivative
CN113058651A
